Pelatihan Laporan Keuangan Berbasis Excel di Lokasi Wisata Bale Tani, Kabupaten Jombang - Wicaksono, Agung Prasetyo Nugroho; Riyanto, Wahyu Hidayat Hidayat; Soelistyo, Aris (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
Financial reports are needed for micro businesses that want to continue to grow to become more professional. This community service program aims to provide Excel-based financial reporting training so that the financial performance of partner businesses is transparent and accountable. Our partners in this community service program are micro businesses at the Bale Tani Tourism location, Banjaragung Village, Bareng District, Jombang Regency. The method of transferring science and technology used in this community service program is ABCD (Asset Based Community Development). The results of this community service program are that partners can gradually apply simple accounting principles and implement accounting technology in the form of Excel-based financial reports in their businesses.